FORMULASI DAN UJI MUTU FISIK SEDIAAN LOTION EKSTRAK KULIT BUAH JAGUNG ( Zea mays L.) - cikra ikhda Nur Hamidah safitri; Luluk Jubaidah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Corn plant is a plant that is widely cultivated in Indonesia. Utilization of corn husk waste so far has only been used as animal feed. Chemical content contained in corn, among others, flavonoids, alkaloids, phenols, steroids, tannins, maysin. This study aims to produce a lotion of corn husk extract and test the physical quality of the lotion preparation. This research consisted of extraction using maceration method with 70% ethanol. Lotion formulation with extract concentrations of 10%, 20% and 30%. Evaluation of the physical quality of the preparations included organoleptic, homogeneity, pH, dispersibility and storage stability tests for 30 days. The results showed that Corn skin extract lotion has a pH of 6, thick form, fine texture, fragrant aroma, light brown color (10%), dark brown (20% and 30%).Texture is homogeneous. The spread of pH test in concentrations of 10%, 20% and 30%, ie 6.3 cm, 6.5 cm, 6.5 cm. The physical quality stability of the lotion stable at room (25°C-30°C) and cold temperature (2°C-8°C). The conclusion of this study is that there is no difference in the three lotions concentrations of 10%, 20% and 30% which are stored at room temperature and cold temperature. Keywords: Corn rind extract, physical quality, lotion